Point Shear Wave Elastography by ElastPQ for Fibrosis Screening in Patients with NAFLD: A Prospective, Multicenter Comparison to Vibration-Controlled Elastography - Bauer, David JM; Matic, Vladimir; Mare, Ruxandra; Maiocchi, Laura; Chromy, David; Müllner-Bucsics, Theresa; Mandorfer, Mattias; Mustapic, Sandra; Sporea, Ioan; Ferraioli, Giovanna; Grgurevic, Ivica; Reiberger, Thomas (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Background Since nonalcoholic fatty liver disease (NAFLD) has become the leading cause of liver disease in the Western world, clinicians need reliable noninvasive tools for the identification of NAFLD-associated fibrosis. Limited evidence on the performance of the novel shear wave elastography technique Elast-PQ (EPQ) in NAFLD is available. Method In this prospective, European multinational study we assessed the diagnostic accuracy of EPQ using vibration-controlled transient elastography (VCTE) as a reference standard. Results Among 353 NAFLD patients, 332 (94.1%) fulfilled reliability criteria of VCTE and EPQ (defined by IQR/median ≤0.3; 41.3% female, mean age: 59 [IQR: 16.5], mean BMI: 29.0 (7.1)). 4/353 (1.1%) and 17/353 (4.8%) had unreliable VCTE and EPQ measurements, respectively. VCTE-based NAFLD fibrosis stages were F0/F1: 222(66.9%), F2: 41 (12.3%), F3: 30 (9.1%), F4: 39 (11.7%). We found a strong correlation (Pearson R=0.87; p<0.0001) and concordance (Lin’s concordance correlation coefficient =0.792) of EPQ with VCTE. EPQ was able to identify NAFLD-fibrosis risk with the following EPQ cutoffs: ≥6.5 kPa for significant fibrosis (≥F2) (≥1.47 m/s; sensitivity: 78%; specificity: 95%; AUROC: 0.94), ≥6.9 kPa for advanced fibrosis (≥F3) (≥1.52 m/s; sens.: 88%, spec.: 89%; AUROC: 0.949), and ≥10.4 kPa for cirrhosis (F4) (≥1.86 m/s; sens.: 87%; spec.: 94%; AUROC: 0.949). Conclusion The point shear wave elastography technique EPQ shows excellent correlation to and concordance with VCTE. EPQ can reliably exclude NAFLD fibrosis <6.0 kPa (<1.41 m/s) and indicate a high risk of advanced fibrosis ≥10.4 kPa (≥1.86 m/s).
Keywords: Abdomen; Gastrointestinal Tract; Point of care; Physics and Technology